1949
DOI: 10.1017/s0022172400014686
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the reaction between horse serum and a pool of rabbit antihorse serum. II. An analysis of the antigens concerned in the production of multiple zones

Abstract: 1. The reaction horse serum and a pool of rabbit antihorse serum exhibiting four α procedure optima has been investigated with a view to analysing the antigens involved in the production of the multiple zones.2. The following conclusions have been reached regarding the antigenic constitution of horse serum, a horse serum-albumin preparation and a horse serum-globulin preparation: Horse serum consists of at least five antigens. The horse serum-albumin preparation contains three antigens, two of which are probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1950
1950
1950
1950

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…When anti-horse sera are titrated against preparations of horse-serum albumin and horse-serum globulin, multiple zones are also frequently observed (Taylor et al 1932;Naylor, 1950), indicating that preparations of horse-serum derivatives contain a number of antigens. * Crystalbumin, a highly purified derivative of horse serum, shows two zones of reaction with the majority of anti-horse sera when titrated by the method of optimal proportions.…”
Section: Introduction To the Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…When anti-horse sera are titrated against preparations of horse-serum albumin and horse-serum globulin, multiple zones are also frequently observed (Taylor et al 1932;Naylor, 1950), indicating that preparations of horse-serum derivatives contain a number of antigens. * Crystalbumin, a highly purified derivative of horse serum, shows two zones of reaction with the majority of anti-horse sera when titrated by the method of optimal proportions.…”
Section: Introduction To the Experimental Methodsmentioning
confidence: 99%
“…Therefore the main zone of the reaction, occurring with far lower concentrations of the mixed antigen than the secondary zone, probably represents a reaction involving the major antigenic component of the crystalbumin preparation. Naylor (1950), working with preparations of horse-serum albumin and horse-serum crystalbumin of the same protein content and a pool of rabbit anti-horse sera, showed that * Since the nomenclature of the proteins present in animal sera is capable of misinterpretation, definition of the terms used is necessary . In this paper the term albumin refers to a protein constituent of horse serum which, though not necessarily homogeneous, probably consists of very similar molecules and is considered to behave as a single antigen.…”
Section: Introduction To the Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations